Nerve Conduction Study of Newly Diagnosed Type 2 Diabetic Patients and Its Correlation with Glycosylated Hemoglobin (HbA1c) (Bangladesh Journal of Neuroscience, 2026)
Background: Peripheral neuropathy is one of the common complications of DM may proceed by a long period of clinically silent impaired glucose tolerance, altering the nerve function by the time diabetes is diagnosed. Nerve conduction study (NCS) remainsthe most reliable, accurate and sensitive measure for diagnosis of peripheral neuropathy. Objectives: Evaluation of nerve conduction study of newly diagnosed type -2 diabetic patients either and to find out its correlation with glycosylated hemoglobin (HbA1c).Method: This case control study, 50 newly diagnosed type-2 diabetic patients within 1 month of both sex and rest 50 healthy controls were studied during 2018-2020 from outpatient department of Endocrinology and advised to attend the department ofNeurology of Dhaka medical college hospital. Nerve conduction study of cross limbs was performed. Blood sugar and glycosylated hemoglobin (HbA1C) were determined.Results: Motor nerve conduction parameters are more affected. Median nerve impairment in both motor and sensory nerve conduction study was statistically significant (p10%. Combined tibial and peroneal nerve involvements were more common 11 (22.0%). In multivariate regression analysis, HbA1C significantly (p